A CFTR Potentiator in Patients with Cystic Fibrosis and the G551D Mutation - Ramsey, Bonnie W; Davies, Jane; McElvaney, N. Gerard; Tullis, Elizabeth; Bell, Scott C; Dřevínek, Pavel; Griese, Matthias; McKone, Edward F; Wainwright, Claire E; Konstan, Michael W; Moss, Richard; Ratjen, Felix; et al. (The New England journal of medicine, 2011)
Ivacaftor, a potentiator of CFTR, was studied in patients with cystic fibrosis (CF) who had mutations that reduced the function of the CFTR protein. Ivacaftor significantly improved FEV 1 and reduced pulmonary exacerbations; it holds promise in the treatment of selected patients with CF. Cystic fibrosis, the most common lethal genetic disease in whites, affects approximately 70,000 people worldwide. 1 – 3 There is no cure for this disease, and the progressive lung disease associated with it is the leading cause of death. Current treatments for cystic fibrosis target the secondary effects of dysfunction of the cystic fibrosis transmembrane conductance regulator (CFTR) protein. The CFTR protein is an epithelial ion channel contributing to the regulation of absorption and secretion of salt and water in various tissues, including the lung, sweat glands, pancreas, and gastrointestinal tract. 4 , 5 Cystic fibrosis is caused by mutations in CFTR that affect . . .